Monitoring Urban Development in Singapore. [Interview] - (:unkn) unknown (Steiner, 2021)
In this interview, Mr Khoo Teng Chye shares some insights on how Singapore has taken a sytem of approach to integrated planning and urban governance at various scales in the city-state's urban development. Through examples on greenerey, public spaces, security and inclusivity, he explains how singapore's methodology has resulted in liveable city outcomes that are well-aligned with the Sustainable Development Goals.
Keywords: Nachhaltige Stadtentwicklung; Integrierte Planung; Urban Governance; Monitoring; Internationaler Vergleich; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung